2008
DOI: 10.1029/2007gl032182
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the non‐hydrostatic effect on the upper atmosphere using a general circulation model (GCM)

Abstract: Under hydrostatic equilibrium, a typical assumption used in global thermosphere ionosphere models, the pressure gradient in the vertical direction is exactly balanced by the gravity force. Using the non‐hydrostatic Global Ionosphere Thermosphere Model (GITM), which solves the complete vertical momentum equation, the primary characteristics of non‐hydrostatic effects on the upper atmosphere are investigated. Our results show that after a sudden intense enhancement of high‐latitude Joule heating, the vertical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
115
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(117 citation statements)
references
References 14 publications
2
115
0
Order By: Relevance
“…Therefore, currently M-GITM does not include the calculation of hydrogen. There is no hydrostatic assumption in this model; thus, it can deal with large vertical velocities [Ridley et al, 2006;Deng et al, 2008]. It is noteworthy that the previous Mars Thermospheric General Circulation Model (M-TGCM) is based on the hydrostatic assumption [ Bougher et al, 2000Bougher et al, , 2006 and thus cannot deal with large vertical winds appropriately, especially when experiencing extreme events, such as interplanetary coronal mass ejections (ICMEs) and solar energetic particles (SEPs) heating.…”
Section: Mars Global Ionosphere Thermosphere Modelmentioning
confidence: 99%
“…Therefore, currently M-GITM does not include the calculation of hydrogen. There is no hydrostatic assumption in this model; thus, it can deal with large vertical velocities [Ridley et al, 2006;Deng et al, 2008]. It is noteworthy that the previous Mars Thermospheric General Circulation Model (M-TGCM) is based on the hydrostatic assumption [ Bougher et al, 2000Bougher et al, , 2006 and thus cannot deal with large vertical winds appropriately, especially when experiencing extreme events, such as interplanetary coronal mass ejections (ICMEs) and solar energetic particles (SEPs) heating.…”
Section: Mars Global Ionosphere Thermosphere Modelmentioning
confidence: 99%
“…GITM can also be run both globally and regionally. One limitation of GITM is the small time step (2-3 s), due to its explicit solver and the presence of vertically propagating acoustic waves in the solution (Deng et al, 2008), while other hydrostatic implicit GCMs may be run with much larger time steps (2-5 min).…”
Section: Methodsmentioning
confidence: 99%
“…Upper atmospheric non-hydrostatic models (Chang and St.-Maurice, 1991;Deng et al, 2008Deng et al, , 2011 showed that sudden enhancements of Joule heating during geomagnetically disturbed periods generate intensive acoustic waves. Meanwhile, significant amounts of energy are deposited in the thermosphere through the acoustic waves propagating from the lower atmosphere (Hickey et al, 2001;Rind, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…These extensions are based on the improved retrospective cost algorithm given in [8], which requires less modeling information than prior versions of this algorithm. This distinction is crucial for GITM, which is a highly nonlinear simulation code, whereas RCSI was originally developed in [5] for linear models.…”
Section: Introductionmentioning
confidence: 99%
“…The grid structure within GITM is fully parallel and covers the entire surface of the Earth by using a block-based two-dimensional domain decomposition in the horizontal coordinates [5]. The number of latitude and longitude blocks can be specified at run time in order to modify the horizontal resolution.…”
Section: Introductionmentioning
confidence: 99%